Repellent effects of Makal, Trichosanthes palmata seed and leaf extracts against Tribolium castaneum (Herbst) and Tribolium confusum Duval - Khanam, LAM; Khan, AR; Khalequzzaman, M; Rahman, SM (University Journal of Zoology, Rajshahi University, 2007)
Key words: Trichosanthes palmata; repellency; Tribolium castaneum; Tribolium confusum Univ. j. zool. Rajshahi Univ. Vol.24, 2005. pp. 31-34